Increasing compound drought and hot event over the Tibetan Plateau and its effects on soil water - Di Wu; Zeyong Hu (Ecological Indicators, 2023)
Climate extremes, such as droughts and hot events, are expected to become more frequent and intense as the Earth’s climate continues to change. Indeed, they will likely pose increasingly serious threats to both humanity and the sustainability of natural ecosystems. Compound climate extremes may significantly impact regions sensitive to climate change, such as the Tibetan Plateau (TP), although there is currently a notable lack of research on compound extreme drought and hot events (CEDHs) that affect this region. We employed the copula model using the standardized precipitation index (SPI), standardized temperature index (STI), and standardized soil moisture index (SSMI) to explore patterns of changes in CEDHs and assess the risk of soil water scarcity under CEDHs. Our results showed that the probability of CEDHs increased significantly across the TP over time, mainly due to hot events becoming more common. The conditional probability of soil water scarcity (SSMI < -0.8) under moderate CEDHs (defined as SPI <  − 0.8 and STI > 0.8) increased by 81.8% and 21.4% over time compared with those under individual hot and dry conditions, respectively. Our findings have important implications for mitigating the impacts of CEDHs under future global warming scenarios.